Enquiring into a teacher performance assessment: towards intelligent professional responsibility in initial teacher education (UCL Press, 2022)
Teacher education is broadly seen as a policy problem in that it has failed to produce sufficient 'classroom ready' teachers. One accountability measure that has been introduced in Australia to address this purported problem is the capstone teacher performance assessments (TPAs). All Australian pre-service teachers must pass this hurdle assessment to be eligible for teacher registration, and all teacher education providers must provide evidence of the effectiveness of their programmes in producing classroom ready teachers to maintain accreditation. The research presented in this article investigated the experiences of a consortium of teacher educators from four Australian universities that implemented a nationally endorsed TPA known as the quality TPA (QTPA). Intelligent professional responsibility was used to consider the experiences and possibilities for educators working in a policy context characterised by increasing accountabilities. Our findings suggest that the introduction of the TPA in Australia created momentum for building collaborative national teacher education partnerships with a focus on improving programme quality and graduate readiness to teach. Our data illustrate how the introduction of a TPA policy mandate in Australia created an external accountability context that allowed for teacher educators to bolster the quality of teacher education programmes from within.